Loss-tolerant cross-Kerr enhancement via modulated squeezing - Tiwari, Ankit; Burgarth, Daniel; Fan, Linran; Guha, Saikat; Arenz, Christian (Optics Express, 2025)
We develop squeezing protocols to enhance cross-Kerr interactions. We show that through alternating between squeezing along different quadratures of a single photonic mode, the cross-Kerr interaction strength can be generically amplified. As an application of the squeezing protocols, we discuss speeding up the deterministic implementation of controlled phase gates in photonic quantum computing architectures. We develop bounds that characterize how fast and strong single-mode squeezing has to be applied to achieve a desired gate error and show that the protocols can overcome photon losses. Finally, we discuss experimental realizations of the squeezing strategies in optical fibers and nanophotonic waveguides.
CRIS-Team Scopus Importer:2025-12-05